Global impacts of energy demand on the freshwater resources of nations - Holland,RA; Scott,KA; Florke,M; Brown,G; Ewers,RM; Famer,E; Kapos,V; Muggeridge,AH; Scharlemann,JPW; Taylor,G; Barrett,J; Eigenbrod,F (Proceedings of the National Academy of Sciences of the United States of America, 2015)
The growing geographic disconnect between consumption of goods, the extraction and processing of resources, and the environmental impacts associated with production activities makes it crucial to factor global trade into sustainability assessments. Using an empirically validated environmentally extended global trade model we examine the relationship between two key resources underpinning economies and human well-being - energy and freshwater. A comparison of three energy sectors (petroleum, gas, electricity) reveals that freshwater consumption associated with gas and electricity production is largely confined within the territorial boundaries where demand originates. This contrasts with petroleum, which exhibits a varying ratio of territorial to international freshwater consumption depending on the origin of demand. For example, while the USA and China have similar demand associated with the petroleum sector, international freshwater consumption is three times higher for the former than the latter. Based on mapping patterns of freshwater consumption associated with energy sectors at subnational scales, our analysis also reveals concordance between pressure on freshwater resources associated with energy production and freshwater scarcity in a number of river basins globally. These energy-driven pressures on freshwater resources in areas distant from the origin of energy demand complicate the design of policy to ensure security of fresh water and energy supply. While much of the debate around energy is focussed on greenhouse gas emissions, our findings highlight the need to consider the full range of consequences of energy production when designing policy.